Mucosal Rugosity Unfolding Technique: A Novel Technique for the Management of Anterior Palatal Fistulae - Muhammad Daiem, MBBS, MD; Nauman Ahmad Gill, MRCS, FCPS; Sadia Nosheen Jan, MBBS, FCPS; Marvee Turk, MD, MPH; Muhammad Ashraf Ganatra, MBBS, MS, MHPE; Muhammad Mustehsan Bashir, MBBS, FCPS, PhD; David Low, MD; Corstiaan Breugem, MD, PhD; Pang-Yun Chou, MD; Ghulam Qadir Fayyaz, MBBS, DSS, MS (Plastic and Reconstructive Surgery, Global Open)
Background:. Palatal fistulae are a well-known complication after palatoplasty. In particular, anterior palatal fistulae (APF) pose a challenge for even the most experienced surgeons. In this study, we present a novel technique for APF repair that leverages the unfurling of epithelialized mucosal folds to lengthen palatal mucoperiosteal flaps so they reach the anterior palate without other complex maneuvers. Methods:. We conducted a retrospective review of patients with APF who presented to a cleft center in Lahore, Pakistan, between 2015 and 2020. Patients without mucosal rugosities on examination were excluded. Data collection included demographic characteristics, physical examination, operative management, and postoperative outcomes. Statistical analyses were conducted using SPSS. Results:. A total of 30 patients with APF were treated using this technique. Patients had an average age at presentation of 11 years (range 3–25 y), with 17 (56.7%) men and 13 (43.3%) women. The average length gained in mucoperiosteal flaps was 12.57 mm on the left and 9.73 mm on the right. Five (16.7%) patients experienced fistula recurrence. Furthermore, 7 (23.3%) patients underwent a concomitant pharyngeal flap for insufficient palatal length at presentation, whereas 6 (20%) were scheduled for one later. Conclusions:. Our study offered a promising single-stage solution for APF closure without donor-site morbidity. Further validation across centers is required to establish this technique as a standard of treatment for APF. However, the presence of a mucosal rugosity is a prerequisite for this technique.